Performing Orders: Speech Acts, Facial Expressions and Gender Bias - Domaneschi, Filippo (Journal of cognition and culture, 2018)
The business of a sentence is not only to describe some state of affairs but also to perform other kinds of speech acts like ordering, suggesting, asking, etc. Understanding the kind of action performed by a speaker who utters a sentence is a multimodal process which involves the computing of verbal and non-verbal information. This work aims at investigating if the understanding of a speech act is affected by the gender of the actor that produces the utterance in combination with a certain facial expression. Experimental data collected show that, as compared to men, women are less likely to be perceived as performers of orders and are more likely to be perceived as performers of questions. This result reveals a gender bias which reflects a process of women’s subordination according to which women are hardly considered as holding the hierarchical social position required for the correct execution of an order